2024
DOI: 10.3390/ijms25020801
|View full text |Cite
|
Sign up to set email alerts
|

GDF15 Protects Insulin-Producing Beta Cells against Pro-Inflammatory Cytokines and Metabolic Stress via Increased Deamination of Intracellular Adenosine

Anongnad Ngamjariyawat,
Jing Cen,
Xuan Wang
et al.

Abstract: It has been proposed that antidiabetic drugs, such as metformin and imatinib, at least in part, promote improved glucose tolerance in type 2 diabetic patients via increased production of the inflammatory cytokine GDF15. This is supported by studies, performed in rodent cell lines and mouse models, in which the addition or production of GDF15 improved beta-cell function and survival. The aim of the present study was to determine whether human beta cells produce GDF15 in response to antidiabetic drugs and, if so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Furthermore, the endogenous upregulation of GDF-15 is associated with resistance to diet-induced obesity, improved glucose homeostasis, and increased insulin sensitivity [69]. In a recent study, GDF-15 was shown to protect insulin-producing beta cells against pro-inflammatory cytokines and metabolic stress [70].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the endogenous upregulation of GDF-15 is associated with resistance to diet-induced obesity, improved glucose homeostasis, and increased insulin sensitivity [69]. In a recent study, GDF-15 was shown to protect insulin-producing beta cells against pro-inflammatory cytokines and metabolic stress [70].…”
Section: Discussionmentioning
confidence: 99%